Internationalism in the olympic movement idea and reality between nations, cultures, and people - Preuss, Holger; Liese, Karsten; SpringerLink (Online service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
The idea of Internationalism has manifested itself not only in the intercultural dialogue within the Olympic Movement, but also at the Olympic Games as the sportive, cultural, and media peak of the four-year-circle. The authors analyze and discuss Internationalism from different professional perspectives, against different cultural backgrounds, as well as in relation to diverse reference groups to widen the understanding of Internationalism as a social interaction in the Olympic Movement. They also aim at establishing the intersections and equal normative principles of Internationalism within the different cultural and institutional fields. These common grounds may be useful for the practical implementation and realization of Internationalism through Olympic sports and at Olympic Youth Camps. This book is valuable reading for academics, practitioners, and policy makers in the field of sport sociology and Olympic studies. - Publisher's description.
Electronic reproduction.
Keywords: Olympics -- Philosophy -- Congresses; Olympics -- Congresses; Internationalism -- Congresses; International cooperation -- Congresses; Electronic books